PDE5 Inhibitors Enhance Celecoxib Killing in Multiple Tumor Types. Issue 5 (May 2015) - Booth, Laurence; Roberts, Jane L.; Cruickshanks, Nichola; Tavallai, Seyedmehrad; Webb, Timothy; Samuel, Peter; Conley, Adam; Binion, Brittany; Young, Harold F.; Poklepovic, Andrew; Spiegel, Sarah; Dent, Paul
<x xml:space="preserve">Abstract</x> The present studies determined whether clinically relevant phosphodiesterase 5 (PDE5) inhibitors interacted with a clinically relevant NSAID, celecoxib, to kill tumor cells. Celecoxib and PDE5 inhibitors interacted in a greater than additive fashion to kill multiple tumor cell types. Celecoxib and sildenafil killed ex vivo primary human glioma cells as well as their associated activated microglia. Knock down of PDE5 recapitulated the effects of PDE5 inhibitor treatment; the nitric oxide synthase inhibitor L‐NAME suppressed drug combination toxicity. The effects of celecoxib were COX2 independent. Over‐expression of c‐FLIP‐s or knock down of CD95/FADD significantly reduced killing by the drug combination. CD95 activation was dependent on nitric oxide and ceramide signaling. CD95 signaling activated the JNK pathway and inhibition of JNK suppressed cell killing. The drug combination inactivated mTOR and increased the levels of autophagy and knock down of Beclin1 or ATG5 strongly suppressed killing by the drug combination. The drug combination caused an ER stress response; knock down of IRE1α/XBP1 enhanced killing whereas knock down of eIF2α/ATF4/CHOP suppressed killing. Sildenafil and celecoxib treatment suppressed the growth of mammary tumors in vivo. Collectively our data demonstrate that clinically achievable concentrations of celecoxib and sildenafil have the potential to be a new therapeutic approach for cancer. J. Cell. Physiol. 230: 1115–1127, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company